Separation and transportation of works using elliptical vibration (Separation of minuscule face- and reverse-side works with a small difference in gap length) - Takashi TANAKA; Yasunori OURA; Yutaka KURITA (Mechanical Engineering Journal)
This study explores the separation and transportation of works using elliptical vibration composed of vertical and horizontal components. When the acceleration amplitude of the vertical component exceeds the jump limit of works on a vibrating table, the works jump. The jump limit varies depending on the gap length at the contact region between the work and the vibrating table. Therefore, face- and reverse-side works can be separated and transported depending on their jump behavior. In this study, the separation and transportation of minuscule face- and reverse-side works were investigated, considering, between both works, the difference in gap length at the contact region. First, the influence of the driving frequency of the elliptical vibration on the jump limit and the positional stability of the jumping works was investigated. Next, the relationship between the transportation velocity and the parameters of the elliptical vibration, particularly the driving frequency and the acceleration amplitude of the horizontal vibration component, was revealed. Finally, experiments on the separation and transportation of minuscule face- and reverse-side works were conducted. By driving the elliptical vibration at a high frequency and high acceleration amplitude of the horizontal vibration component, high-speed and stable separation and transportation of minuscule works were realized.